A Cognitive Uncoupling: Masculinity Threats and the Rejection of Relationship Interdependence. Issue 6 (August 2021) - Lamarche, Veronica M.; Atkinson, Ciara; Croft, Alyssa
What happens when a primary resource people draw from in times of need is at odds with maintaining a threatened, yet valued, identity? Four studies ( N total = 806) examined whether men cognitively disengage from romantic relationships following masculinity threats. As hypothesized, romantically attached men reported less closeness, commitment, and interdependence in their romantic relationships (Study 1), and both single and romantically attached men expressed less positive commitment beliefs (Study 2) following masculinity threats. Supporting a strategy of distancing from interdependence to protect masculinity, perceivers evaluated men who used more interdependent language to describe their relationships as less masculine and more feminine (Studies 3a and 3b). However, exhibiting less interdependence did not restore third-party evaluations of masculinity following a public masculinity threat (Study 3b). Thus, subverting relationship interdependence to protect perceptions of masculinity is an ineffective strategy for restoring masculinity in the eyes of others and may cause unnecessary strain on relationships.